A wireless sensor network deployment to detect the degeneration of cement used in construction. (20th March 2014) - Sendra, S.; Lloret, A.T.; Lloret, J.; Rodrigues, J.J.P.C.
During last few years, the high environmental humidity and salinity in areas close to the sea have caused degeneration of the construction materials. Due to this, several building have collapsed. Several studies demonstrated that it is very difficult to predict these cases. For this reason, we propose a non–invasive technique which takes into account the appropriate placement of the wireless sensors to detect the degeneration of the cement used in construction. Our proposal is based on a wireless sensor network (WSN) which is able to sense the temperature, humidity, micro–vibrations and structural movements. We show the sensor deployment and its appropriate location to take the most suitable measurements and ensure the reliability of the data. We show the energy consumption of each node and the web interface used to show the data. From the structural movements, our WSN can know whether a building is in danger of collapse or not.